Analisa Faktor-faktor yang Mempengaruhi Transaction Cost pada Holding Period Saham Perusahaan yang Terdaftar di Bursa Efek Jakarta (BEJ) - Yuniningsih, Yuniningsih (Jurnal Aplikasi Manajemen, 2008)
The grade level of Holding Period had been importantly noticed by the stock exchange practicians, both the stock holders and the members of the stock exchange, as one of the company success indicators. Te aim of the research is to find out the influence of Bid-Ask Spread, Market Value and Risk of Return partially and simultaneously to the Holding Period of the cigarette manufacturers that had carried out "Go Public" at Jakarta Stock Exchange. Research uses Secondary Data as in the shape of monthly transaction data of the listed companies stocks at Jakarta stock Exchange for the period of 2005. Besides, data can also be received from http://www.jsx.co.id and Capital Market Directory. Applying classical assumption test while, in the same time, using least multiple regressions in data analysis. In order to examine the proposed hypothesis for the early research, both simultaneous test (F test) and partial test (t test) were applied. The result of the research simultaneously showed that the weighty of Bid-Ask Spread, Market Value, and Risk of Return influenced Holding Period with the significance level of 5%. On the other hand, the result of the research partially showed that only Risk of Return variable influenced Holding Period variable. However, neither Bid-Ask Spread nor Market Value influenced Holding Period. It summarizes that investors need 10 pay attention to Risk of Return in the decision making to determine the length of possession for the stocks wit significance level of 0,022 or less than 5%.